Desain Logo sebagai Brand Image pada Digital Marketing Produk UMKM dengan Metode (HCD) Human Centered Design di Desa Pematang Serai - Mohammad Yusup; Arpan; Aidil Ahmad (Jurnal Nasional Teknologi Komputer, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Pematang Serai Village hold significant potential for local economic development, yet they face challenges in establishing a strong brand identity to support digital marketing efforts. This study aims to design logos as visual representations of MSME brand images using the Human Centered Design (HCD) approach, involving both business owners and consumers directly in the design process. The research was conducted through the three main phases of HCD: Inspiration, Ideation, and Implementation. In the Inspiration phase, observations and interviews were conducted with MSME actors and local consumers to explore their needs and visual preferences. During the Ideation phase, several logo design concepts were developed based on the insights gathered and evaluated through focus group discussions. Finally, in the Implementation phase, the finalized logo was applied to digital media such as product packaging and social media platforms. The results show that logos incorporating local cultural elements, natural color palettes, and simple typography can enhance product appeal and convey professionalism in the eyes of consumers. The HCD approach proves effective in producing logos that are not only visually attractive but also emotionally and functionally representative of the product identity. This study contributes to strengthening MSME branding through user-centered and participatory design methods.